2023
DOI: 10.46234/ccdcw2023.041
|View full text |Cite
|
Sign up to set email alerts
|

Hesitancy to Receive the Booster Doses of COVID-19 Vaccine Among Cancer Patients in China: A Multicenter Cross-Sectional Survey — Four PLADs, China, 2022

Abstract: What is already known about this topic? Cancer patients are more vulnerable and have higher mortality rates from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) than the general population; however, coverage for booster doses of the coronavirus disease 2019 (COVID-19) vaccine was low among cancer patients in China. What is added by this report? Overall, 32.0% and 56.4% of cancer patients from four Provincial Level Administrative Divisions (PLADs) expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Our study further demonstrated that negative attitudes towards vaccines and perceived barriers were both associated with reduced acceptance of the second COVID-19 booster Dose. Similar results were found in immunocompromised cancer patients, which strengthened the necessity of vaccination among specific populations ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 79%
“…Our study further demonstrated that negative attitudes towards vaccines and perceived barriers were both associated with reduced acceptance of the second COVID-19 booster Dose. Similar results were found in immunocompromised cancer patients, which strengthened the necessity of vaccination among specific populations ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, recent studies showed that receiving a COVID-19 vaccine booster dose could significantly increase antibody titers among cancer patients and many countries have been recommending a third and a fourth dose of COVID-19 vaccine to cancer patients. 48–50 Therefore, the country may also consider introducing a COVID-19 vaccine booster dose to cancer patients. Many regions have already recommended a third and fourth dose of COVID-19 vaccines to immunodeficiency people, such as cancer patients, including in Hong Kong, China.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, understanding the impact of booster doses on the immune response in PLWH is crucial for optimizing further vaccine strategies and ensuring adequate protection. Moreover, the acceptance of COVID‐19 vaccine is generally low while the risk of infection is high in people with immunodeficiency 25,26 . Of note, concerns for the performance of vaccine is an essential element to affect the willingness of booster doses vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the acceptance of COVID-19 vaccine is generally low while the risk of infection is high in people with immunodeficiency. 25,26 Of note, concerns for the performance of vaccine is an essential element to affect the willingness of booster doses vaccination. Hence, understanding the immunogenicity and safety profiles for the vaccination among PLWH in the real-world would contribute to improving the coverage of vaccination.…”
Section: Introductionmentioning
confidence: 99%